Young people and road user behaviour: attitudes, judgements and behaviour - Adams, J. R. (Cranfield University, 1992)
The problem of the disproportionately high accident and offence rate of young drivers is a major area for concern in the field of road safety (Cameron, 1982,1983; Jonah, 1986). Research suggests that young drivers have a propensity to become involved in risk-taking behaviours and that this may be due to both motivational factors (Schuman, et al, 1967; MacMillan, 1975; Wilde, 1982; Jessor, 1987), and the components of risk perception (Quenault et al, 1968; Quimby and Watts, 1981; Finn and Bragg, 1986; Mathews and Moran, 1986). The present study employed two distinct methodologies (surveys and the relatively novel technique of interactive video) in order to examine the attitudes, judgements and behaviours of a sample of young drivers (17-19 years) and pre-drivers (11-18 years). The questionnaire surveys and the Interactive Video Driving Programme (I. V. D. P. ) revealed that distinct attitudes towards driving are held as early as 11 years of age, and that there are several attitudinal, judgemental and behavioural dimensions along which the sexes and/or the developmental groups within the driver and pre-driver sample, could be discriminated. These dimensions related to perceptions of driving offences, risk-taking attitudes and behaviours, hazard perception and evaluation, and road environment awareness. The use of the I. V. D. P. allowed the examination of driving behaviours and judgements in simulated decision situations. Results indicated that there were some differences in the results produced by the two methodologies. Results tend to suggest that the more interactive and pictorial modes of information presentation may be more successful in assisting young people to develop more accurate mental representations of the road traffic environment. The results are discussed in terms of their implications for the design and implementation of school-based pre/driver education programmes. Specifically, issues such as information content and presentation, and the targeting of information at young people of different developmental stages are addressed.